Comparative study of causative organism in erosive cervicitis, cervical intra epithelial neoplasia and carcinoma cervix using Pap smear - Bindal, Jyoti; Paldiya, Deepak (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Cervical cancer is the third largest cause of cancer mortality in India after cancers of the mouth and oropharynx, and oesophagus, accounting for nearly 10% of all cancer related deaths in the country. Methods: The present study carried out 300 patients in Gajra Raja Medical College in the Department of Obstetrics and Gynaecology, OPD and indoor admitted patients from July 2016 to December. 2016. The selected patients were examined with care to note any cervical lesion, appearance of cervix, nature of any cervical/ vaginal discharge. Then a cervical scrape was taken with an Ayre’s spatula and slide stained and then examined. Results: The maximum cases of HPV were seen in CIN, LSIL and HSIL. Maximum incidence of all cases was seen in the age group of 30-50 yrs. The women married before 18 years had the highest incidence of CIN and HPV infection. Majority of the cases of cervicitis were co-infected with H-Vaginalis and Trichomonas. Most women opted for a sterilization procedure rather than any other method of contraception. Use of no contraception puts these women at a high risk of acquiring HPV infection from infected partners. Conclusions: Occurrence of HPV infection declines with increasing grades. Most of the patients with HPV infection had presented with non-specific symptoms of discharge P/V or lower abdominal pain.